2013
DOI: 10.1021/jp406125x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Binding and Stability of Curcumin in Diamide-Linked γ-Cyclodextrin Dimers

Abstract: Curcumin is a naturally occurring molecule with medicinal properties that is unstable in water, whose efficacy as a drug can potentially be enhanced by encapsulation inside a host molecule. In this work, the thermodynamics and mechanism of binding of curcumin to succinamide- and urea-linked γ-cyclodextrin (γ-CD) dimers in water are investigated by molecular dynamics simulations. The simulated binding constants of curcumin to succinamide- and urea-linked γ-CD dimers at 310 K are 11.3 × 10(6) M(-1) and 1.6 × 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…56,57 Moreover, a recent computational study has shown the presence of water molecules and diffusive motions of curcumin within the γ-CD cavities of 66γCD 2 su and 66γCD 2 ur. 55 In addition, our previous 2D NOESY 1 H NMR spectroscopic results show the intermolecular alkyl hydrogen-hydrogen interactions between curcumin and the γ-CD moieties of 66γCD 2 su and 66γCD 2 ur. 29 In short, the slow relaxation dynamics of 66γCD 2 su-curcumin and 66γCD 2 ur-curcumin complexes may be derived from fluctuations of the γ-CD moieties, reorientation of constrained water molecules, diffusive motions of curcumin within the γ-CD a The transient absorption kinetics were fitted with the multiexponential function, f(t) = ∑ i = 1 n a i exp(−t/τ i ), where ∑ i = 1 n |a i | = 1, with the minimum number of exponential terms (n).…”
Section: ■ Materials and Methodsmentioning
confidence: 84%
“…56,57 Moreover, a recent computational study has shown the presence of water molecules and diffusive motions of curcumin within the γ-CD cavities of 66γCD 2 su and 66γCD 2 ur. 55 In addition, our previous 2D NOESY 1 H NMR spectroscopic results show the intermolecular alkyl hydrogen-hydrogen interactions between curcumin and the γ-CD moieties of 66γCD 2 su and 66γCD 2 ur. 29 In short, the slow relaxation dynamics of 66γCD 2 su-curcumin and 66γCD 2 ur-curcumin complexes may be derived from fluctuations of the γ-CD moieties, reorientation of constrained water molecules, diffusive motions of curcumin within the γ-CD a The transient absorption kinetics were fitted with the multiexponential function, f(t) = ∑ i = 1 n a i exp(−t/τ i ), where ∑ i = 1 n |a i | = 1, with the minimum number of exponential terms (n).…”
Section: ■ Materials and Methodsmentioning
confidence: 84%
“…Unlike the traditional Amber force fields, general Amber force field (GAFF) is more general for organic chemical [21]. Some recent articles chose GAFF force fields in MD simulation of CDs [22][23][24]. So the GAFF force field was selected in Antechamber module with AM1-BCC charge method for all molecules.…”
Section: Simulationmentioning
confidence: 99%
“…All MD preparations and simulations were performed by AmberTools 15 program . Some recent articles chose general amber force fields in MD simulation for CDs . Hence, the general amber force field with AM1‐BCC charge model was used for all molecules by Antechamber module.…”
Section: Methodsmentioning
confidence: 99%